Upscaling Strategies of Porosity-Permeability Correlations in Reacting Environments from Pore-Scale Simulations. (19th June 2018) - Prasianakis, Nikolaos I.; Gatschet, Michael; Abbasi, Aida; Churakov, Sergey V.
Abstract : In geochemically reacting environments, the mineral dissolution and precipitation alters the structural and transport properties of the media of interest. The chemical and structural heterogeneities of the porous media affect the temporal evolution of the permeability with respect to porosity. Such correlations follow a nonlinear trend, which is difficult to estimate a priori and without knowledge of the microstructure itself, especially under the presence of strong chemical gradients. Macroscopic field-scale codes require such an input, and in the absence of exact descriptions, simplified correlations are used. After highlighting the diversity of microstructural evolution paths, due to dissolution, we discuss possible upscaling strategies.